Hydrogen-natural gas fuel blending in a “rich burn” engine with 3-way catalyst - Katsampes, Nicholas; Montgomery, David; Arney, Gregg; Olsen, Daniel B. (Frontiers in Fuels, 2024)
Interest in hydrogen (H2) fuels is growing, with industry planning to produce it with stranded or excess energy from renewable sources in the future. Natural gas (NG) utility companies are now taking action to blend H2 into their preexisting pipelines to reduce greenhouse gas (GHG) emissions from burning NG. Stoichiometric (“rich burn”) NG engines that operate on pipeline NG and will receive blended fuel as more gas utilities expand H2 production. These engines are typically chosen for their low emissions owing to the 3-way catalyst control, so the focus of this paper is on the change in emissions like carbon monoxide (CO) and nitrogen oxides (NOx) as the fuel is blended with up to 30% H2 by volume. The Caterpillar CG137-8 natural gas engine used for testing was originally designed for industrial gas compression applications and is a good representative for most “rich burn” engines used across industry for applications such as power generation, gas compression, and water pumping. A significant greenhouse gas (GHG) emissions reduction is observed as more H2 is added to the fuel. Increasing H2 in the fuel changes combustion behavior in the cylinder, resulting in faster ignition and higher cylinder pressures, which increase engine-out NOx emissions. Post-catalyst CO and NOx both decrease slightly with increasing H2 while operating at the optimal “air-fuel” equivalence ratio (λ). A “rich burn” engine with 3-way catalyst can tolerate up to 30% H2 (by vol.) while still meeting NOx and CO emissions limits. However, at elevated levels of H2, increased engine-out NOx emissions narrow the λ range of operation. As H2 is added to NG pipelines, some “rich burn” engine systems may require larger catalysts or more precise λ control to accommodate the increased NOx production associated with a H2-NG blend. Sudden step-increases in H2 cause dramatic changes in λ, resulting in large emissions of post-catalyst NOx during the transition. Comparable changes in H2 at elevated concentrations cause larger spikes in NOx than at lower concentrations. Better tuned engine controllers respond more quickly and produce less NOx during H2 step-transitions.